Tw~n lalhqhsome/nwn in Hebrews 3,5 - Swetnam, James (Biblica, 2009)
The words tw~n lalhqhsome/nwn in Heb 3,5 allude to the words of Christ at the institution of the Eucharist. This is argued from 1) the contrast between Christ and Moses in Heb 3,1-6 as understood against the background of Num 12,7[LXX]; 2) the thematic use of lale/w in Hebrews; 3) the relevance of Heb 9,20; 4) the place of Heb 3,5 in the structure of Heb 1,1–3,6. All to be understood against a Eucharistic interpretation of Heb 2,12 and Heb 13.